Aesthetic features of the art of decoupage and their representations in the productions of art education students - Haneen ali salam; Malik hameed muhsin (الاكاديمي, 2024)
This research dealt with the study of the aesthetic features of the art of decoupage and their representations in the products of art education students. In the importance of the research, the two researchers touched on the need that prompted them to adopt this topic. As for the goal of the research, it started from the title and the problem, as follows: (Discovering the aesthetic features of the art of decoupage and their representations in the productions of art education students). The two researchers defined the limits of the research, which were represented by the students of the Department of Art Education / College of Fine Arts / University of Baghdad 2022_2023 AD. The researchers also defined the terms in the light of the nature of the current research, including: (characterization, beauty, the art of decoupage) idiomatically and procedurally, then the researchers moved to the second chapter, which Two sections included the first dealing with the study of the concept of the aesthetic feature, touching on some philosophical ideas that pertain to the subject of beauty for artistic achievements, and also with regard to some aesthetic opinions between philosophers of beauty and art, as well as addressing the most important aesthetic features, while the second topic discussed the concept of decoupage art and the most important types of this art, He also touched on some of the number and tools used, and the researchers extracted their indications about the theoretical framework represented by this chapter and paved the way for the third chapter, which included the research procedures. The fourth is based on the results of the research, recommendations, and proposals, and through the findings of the study, and after the analysis process, the two researchers reviewed their results, which are as follows: 1 - The aesthetic features (aesthetic emotion) were taken as a basis for them in the process of formal synthesis, the psychological or psychological context and the pure aesthetic context. 2 - The aesthetic feature of the artistic achievement in the art of decoupage came according to a different tactile context and a different raw context (various materials). The researchers also reached several conclusions regarding the aesthetic features in the artistic achievements, and then reviewed the proposals.